2023
DOI: 10.1039/d2fo02928f
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of table olives exerts antihypertensive effects in association with changes in gut microbiota in spontaneously hypertensive rats

Abstract: Arbequina table olive (AO) consumption lowers blood pressure (BP) in spontaneously hypertensive rats (SHR). This study evaluates whether dietary supplementation with AO induced changes in the gut microbiota that are...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
(115 reference statements)
0
1
0
Order By: Relevance
“…The doses administered to the rats are equivalent to the human consumption of 30 and 60 Arbequina table olives and were selected because the intake of 30 olives was double to one serving according to the Mediterranean diet pyramid . Moreover, this dosage is relevant to health because the administration of 3.85 g/kg to spontaneously hypertensive rats decreased blood pressure, being the antihypertensive effect associated with changes in the concentration of angiotensin II, malondialdehyde as well as gut microbiota remodeling . Our results have demonstrated that hydroxytyrosol provided in table olives, although extensively metabolized, remained in plasma during 8 h. Therefore, table olives can be considered an efficient vehicle to deliver hydroxytyrosol, thus, emerging as a functional food.…”
Section: Introductionmentioning
confidence: 74%
“…The doses administered to the rats are equivalent to the human consumption of 30 and 60 Arbequina table olives and were selected because the intake of 30 olives was double to one serving according to the Mediterranean diet pyramid . Moreover, this dosage is relevant to health because the administration of 3.85 g/kg to spontaneously hypertensive rats decreased blood pressure, being the antihypertensive effect associated with changes in the concentration of angiotensin II, malondialdehyde as well as gut microbiota remodeling . Our results have demonstrated that hydroxytyrosol provided in table olives, although extensively metabolized, remained in plasma during 8 h. Therefore, table olives can be considered an efficient vehicle to deliver hydroxytyrosol, thus, emerging as a functional food.…”
Section: Introductionmentioning
confidence: 74%
“…Furthermore, our study demonstrated that the RPP intervention led to a significant downregulation of the amount of Ruminococcus, as well as the conditionally pathogenic bacterium Bacteroides. Ruminococcus is known to produce inflammatory polysaccharides that disrupt intestinal barrier function [46], and its reduction has been associated with improved hypertension [47]. These results suggest that RPPs could contribute to the maintenance of gut microbiota stability.…”
Section: Discussionmentioning
confidence: 93%